Adhesive sheet and optical laminate
By adjusting the mixing amount of the hydroxy monomer and isocyanate crosslinking agent in the photocurable composition, the problem of low anchoring force between the adhesive sheet and the optical film is solved, and higher anchoring force, lower energy consumption and CO2 emissions are achieved.
Patent Information
- Application Number
- CN202380055542.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-22
- Filing Date
- 2023-07-21
- Publication Date
- 2025-03-07
AI Technical Summary
The existing bond sheet manufacturing process requires a large amount of fuel combustion, resulting in high energy consumption and CO2 emissions. At the same time, the bond sheet and optical film formed by the photocuring method have little anchoring force and are easy to peel off.
By adjusting the mixing amount of the hydroxyl-containing monomer and isocyanate-based crosslinking agent, an appropriate photocurable composition is formed, ensuring that the adhesive sheet continues to cure after being bonded to the optical film, thereby increasing the anchoring force.
The anchoring force between the adhesive sheet and the optical film is effectively improved, the peeling phenomenon between the adhesive sheet and the optical film is reduced, and the energy consumption and CO2 emissions of the manufacturing process are reduced.
Smart Images

Figure CN119585381A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a pressure-sensitive adhesive sheet and an optical laminate. Background Art
[0002] Various image display devices represented by liquid crystal display devices and electroluminescent (EL) display devices generally have an optical laminate including an optical film such as a polarizing film and an adhesive sheet. Adhesive sheets are usually used to bond the optical films contained in the optical laminate and to bond the optical laminate to the image display panel. As an adhesive sheet, a typical sheet is obtained by curing a monomer group including an acrylic monomer, a silicone monomer, etc. by polymerization and crosslinking.
[0003] An example of a PSA sheet is disclosed in Patent Document 1. In Patent Document 1, the PSA sheet is produced by irradiating a PSA composition with light.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent No. 3052972 Summary of the invention
[0007] Problems to be solved by the invention
[0008] A general adhesive sheet can be manufactured by, for example, the following thermal curing method. First, a crosslinking agent is added to a polymer obtained by polymerizing a polymerizable monomer in an organic solvent to prepare an adhesive composition. The adhesive composition is applied to a substrate such as a release liner, and the organic solvent is removed by heating to form a sheet. Heating and aging are performed as required to complete crosslinking, thereby enabling the manufacture of an adhesive sheet. In this manufacturing process, in order to generate the heat energy required for heating and aging of the solvent, a large amount of fuel such as LNG needs to be burned. In addition, if the organic solvent removed by heating is directly discharged into the atmosphere, there is a hidden danger of causing serious adverse effects on the surrounding environment. Therefore, for organic solvents, in most cases, they are released after being burned in a deodorizing furnace or the like. In this case, not only does the fuel used for burning in the deodorizing furnace become more necessary, but the organic solvent itself is also converted into CO2 due to combustion and discharged into the atmosphere, which is a manufacturing process with a very large CO2 emission.
[0009] In recent years, climate change caused by greenhouse gases has become an urgent issue, and governments around the world have set numerical targets to reduce CO2. In the manufacture of adhesive sheets, it is also required to select a manufacturing process that does not use organic solvents and has low CO2 emissions.
[0010] Compared with the above-mentioned thermal curing method, the method of making an adhesive sheet using light (photocuring method) can reduce the energy required for forming the adhesive sheet and the amount of CO2 emissions. However, when an optical laminate is made using an adhesive sheet formed by the photocuring method, there is a tendency that the anchoring force between the adhesive sheet and the optical film is small and peeling easily occurs between the adhesive sheet and the optical film.
[0011] Therefore, the present invention provides a pressure-sensitive adhesive sheet suitable for adjusting the anchoring force with an optical film to a large value.
[0012] Solutions to the problem
[0013] According to the research of the inventors, when an adhesive sheet formed by a photocuring method is used, there is a tendency that peeling between the adhesive sheet and the optical film is more likely to occur than when an adhesive sheet formed by a thermal curing method is used. It can be inferred that the reason for this tendency is that when an adhesive sheet formed by a thermal curing method is bonded to an optical film, the curing of the adhesive sheet further proceeds on the surface of the optical film, while on the other hand, the curing of the adhesive sheet formed by a photocuring method after bonding to the optical film is hardly performed. This problem occurs particularly significantly when the optical film includes a uniaxially stretched film such as a polarizer and the thickness of the adhesive sheet is less than 30 μm.
[0014] Based on the above insights, the inventors conducted further research and found that if the amount of hydroxyl-containing monomers and isocyanate cross-linking agents is appropriately adjusted, even when an adhesive sheet formed from a photocurable composition is used, the curing of the adhesive sheet will further proceed after being bonded to the optical film, thereby adjusting the anchoring force to the optical film to a larger value, thereby completing the present invention.
[0015] The present invention provides an adhesive sheet formed from a photocurable composition containing a monomer group and / or a partial polymer of the monomer group.
[0016] In 100 parts by weight of the above monomer group, the amount of the hydroxyl-containing monomer is less than 5 parts by weight.
[0017] The photocurable composition comprises an isocyanate crosslinking agent.
[0018] The amount of the isocyanate crosslinking agent is 0.02 parts by weight or more based on 100 parts by weight of the total of the monomer group and the partial polymer.
[0019] Furthermore, the present invention provides an optical layered body comprising:
[0020] The above adhesive sheet, and
[0021] An optical film including at least one selected from a polarizing film and a retardation film.
[0022] Effects of the Invention
[0023] According to the present invention, it is possible to provide a pressure-sensitive adhesive sheet suitable for adjusting the anchoring force with an optical film to a large value. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a cross-sectional view schematically showing an example of the pressure-sensitive adhesive sheet of the present invention.
[0025] Figure 2A This is a schematic diagram for explaining a method for measuring the creep amount of a PSA sheet.
[0026] Figure 2B This is a schematic diagram for explaining a method for measuring the creep amount of a PSA sheet.
[0027] Figure 3A This is a schematic diagram for explaining an example of the method for producing the pressure-sensitive adhesive sheet of the present invention.
[0028] Figure 3B This is a schematic diagram for explaining an example of the method for producing the pressure-sensitive adhesive sheet of the present invention.
[0029] Figure 3C This is a schematic diagram for explaining an example of the method for producing the pressure-sensitive adhesive sheet of the present invention.
[0030] Figure 4 This is a cross-sectional view schematically showing an example of the optical layered body of the present invention.
[0031] Figure 5 This is a cross-sectional view schematically showing an example of the optical layered body of the present invention. DETAILED DESCRIPTION
[0032] The adhesive sheet of the first embodiment of the present invention is formed of a photocurable composition containing a monomer group and / or a partial polymer of the monomer group.
[0033] In 100 parts by weight of the above monomer group, the amount of the hydroxyl-containing monomer is less than 5 parts by weight.
[0034] The photocurable composition comprises an isocyanate crosslinking agent.
[0035] The amount of the isocyanate crosslinking agent is 0.02 parts by weight or more based on 100 parts by weight of the total of the monomer group and the partial polymer.
[0036] In the second aspect of the present invention, for example, in the pressure-sensitive adhesive sheet of the first aspect, the amount of the isocyanate crosslinking agent blended is 0.1 parts by weight or more based on 100 parts by weight of the total of the monomer group and the partial polymer.
[0037] In a third aspect of the present invention, for example, in the pressure-sensitive adhesive sheet of the first or second aspect, the amount of isocyanate groups in the photocurable composition relative to the amount of hydroxyl groups in the photocurable composition is 0.02 or more.
[0038] In a fourth aspect of the present invention, for example, in the pressure-sensitive adhesive sheet according to any one of the first to third aspects, the isocyanate crosslinking agent includes an aliphatic isocyanate compound and / or a derivative of the aliphatic isocyanate compound.
[0039] In a fifth aspect of the present invention, for example, in the pressure-sensitive adhesive sheet of any one of the first to fourth aspects, the isocyanate crosslinking agent is at least one selected from pentamethylene diisocyanate crosslinking agents and hexamethylene diisocyanate crosslinking agents.
[0040] In a sixth aspect of the present invention, for example, in the pressure-sensitive adhesive sheet according to any one of the first to fifth aspects, the content of the solvent in the photocurable composition is 5% by weight or less.
[0041] In a seventh aspect of the present invention, for example, in the pressure-sensitive adhesive sheet according to any one of the first to sixth aspects, the monomer group includes a (meth)acrylic monomer.
[0042] In an eighth aspect of the present invention, for example, in the PSA sheet according to any one of the first to seventh aspects, the concentration of the residual monomers is 16000 ppm by weight or less.
[0043] In a ninth aspect of the present invention, for example, the pressure-sensitive adhesive sheet according to any one of the first to eighth aspects has a surface subjected to a surface modification treatment.
[0044] The optical layered body according to the tenth aspect of the present invention includes:
[0045] The pressure-sensitive adhesive sheet according to any one of the first to ninth aspects, and
[0046] An optical film including at least one selected from a polarizing film and a retardation film.
[0047] In the 11th aspect of the present invention, for example, in the optical laminate of the 10th aspect, the anchoring force between the pressure-sensitive adhesive sheet and the optical film is 10.0 N / 25 mm or more.
[0048] Hereinafter, the present invention will be described in detail, but the present invention is not limited to the following embodiments and can be implemented with arbitrary modifications within the scope not departing from the gist of the present invention.
[0049] [Embodiments of Adhesive Sheet]
[0050] An example of the pressure-sensitive adhesive sheet of this embodiment is shown in Figure 1 . Figure 1 The adhesive sheet 1 is formed from a photocurable composition comprising a monomer group and / or a partial polymer of the monomer group. In the photocurable composition, the amount of the hydroxyl-containing monomer in 100 parts by weight of the monomer group is less than 5 parts by weight. In addition, the photocurable composition contains an isocyanate crosslinking agent, and the amount of the isocyanate crosslinking agent is 0.02 parts by weight or more relative to 100 parts by weight of the total of the monomer group and the partial polymer.
[0051] In the case of using a photocurable composition in which the amount of a hydroxyl-containing monomer and an isocyanate crosslinking agent is adjusted to the above range, when forming the adhesive sheet 1, there is a tendency to suppress the reaction of the isocyanate crosslinking agent with the hydroxyl-containing monomer or a partial polymer having a structural unit from the monomer. By suppressing the reaction, the isocyanate crosslinking agent is not easily consumed immediately. Thus, in the adhesive sheet 1 formed by the photocurable composition, there is a tendency for the isocyanate crosslinking agent to remain. In the case of laminating the adhesive sheet 1 to the optical film, there is a tendency for the curing of the adhesive sheet 1 to proceed further after laminating. And by further carrying out the curing of the adhesive sheet 1 on the surface of the optical film, the anchoring force between the adhesive sheet 1 and the optical film can be adjusted to a larger value.
[0052] like Figure 1 As shown, the adhesive sheet 1 has surfaces 1a and 1b facing each other. As an example, the adhesive sheet 1 is attached to the optical film via the surface 1a, and the adhesive sheet 1 is attached to the image display panel via the surface 1b. The surface 1a of the adhesive sheet 1 in contact with the optical film may be subjected to a surface modification treatment or may not be subjected to a surface modification treatment. According to the surface 1a subjected to the surface modification treatment, there is a tendency to improve the anchoring force between the adhesive sheet 1 and the optical film. On the other hand, it is preferred that the surface 1b of the adhesive sheet 1 is not subjected to a surface modification treatment. As the surface modification treatment, corona treatment, plasma treatment, excimer treatment, flame treatment, etc. can be cited. The surface 1a is preferably subjected to a corona treatment as a surface modification treatment.
[0053] The surface modification treatment may be implemented in an inert gas atmosphere. By performing the surface modification treatment in a state where the oxygen concentration is reduced by using an inert gas, the risk of ignition of the residual monomer can be reduced. Specifically, the surface modification treatment is preferably performed at an oxygen concentration of 8% by volume or less, more preferably 6% by volume or less, and further preferably 3% by volume or less. If the oxygen concentration is too low, it may cause the introduction of functional groups to the surface of the adhesive sheet by the surface modification treatment to become insufficient, and therefore, the oxygen concentration is preferably 0.01% by volume or more, more preferably 0.1% by volume or more, and particularly preferably 0.5% by volume or more. As specific examples of inert gases, nitrogen and argon can be cited. The surface modification treatment can be implemented at normal pressure (1 atmosphere).
[0054] The conditions of the surface modification treatment as the corona treatment are represented by the discharge amount, for example, 0.6 to 100 kJ / m 2 The lower limit of discharge can be 1kJ / m 2 Above, 2kJ / m 2 Above, 5kJ / m 2 Above, 7kJ / m 2 Above, 10kJ / m 2 Above, 13kJ / m 2 Above, 15kJ / m 2 Above, 20kJ / m 2 Above, 25kJ / m 2 Above, 30kJ / m 2 Above, it can be 35kJ / m 2 The upper limit of the discharge amount can be 70 kJ / m 2 Below, 60kJ / m 2 Below, 50kJ / m 2 Below, 45kJ / m 2 Below, 40kJ / m 2 Below, 30kJ / m 2 Below, 20kJ / m 2 Below, and further can be 18kJ / m 2 When the corona treatment is performed in an atmosphere with an oxygen concentration of 10 volume % or more and 20.9 volume % or less, the discharge amount can be 1 to 18 kJ / m 2 When the corona treatment is performed in an atmosphere having an oxygen concentration of 0.01 volume % or more and less than 10 volume %, the discharge amount may be 1 to 60 kJ / m 2 By appropriately adjusting the discharge amount of the corona treatment, there is a tendency for the anchoring force between the pressure-sensitive adhesive sheet 1 and the optical film to be further improved.
[0055] (Photocurable composition)
[0056] As described above, the adhesive sheet 1 is formed by a photocurable composition. The photocurable composition is an adhesive composition that forms the adhesive sheet 1 by irradiating light. In the photocurable composition, the monomer group includes, for example, a (meth)acrylic monomer. The content of the (meth)acrylic component in the photocurable composition, that is, the (meth)acrylic monomer and its partial polymer, can be 50% by weight or more, 60% by weight or more, 70% by weight or more, and further can be 80% by weight or more. In this case, an acrylic adhesive sheet 1 with (meth)acrylic polymer and its cross-linked product as the main component can be formed. However, the photocurable composition is not limited to the above examples. In this specification, (meth)acrylic acid refers to acrylic acid and methacrylic acid. (Meth)acrylate refers to acrylate and methacrylate.
[0057] Examples of (meth)acrylic monomers include (meth)acrylic acid alkyl esters having an alkyl group having 1 to 20 carbon atoms in a side chain. The number of carbon atoms in the alkyl group may be 7 or less, 6 or less, 5 or less, or 4 or less. The alkyl group may be linear or branched. Examples of the alkyl (meth)acrylates are methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, isobutyl (meth)acrylate, n-pentyl (meth)acrylate, isopentyl (meth)acrylate, n-hexyl (meth)acrylate, isohexyl (meth)acrylate, isoheptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, n-nonyl (meth)acrylate, isononyl (meth)acrylate, n-decyl (meth)acrylate, isodecyl (meth)acrylate, n-dodecyl (meth)acrylate (lauryl (meth)acrylate), n-tridecyl (meth)acrylate, n-tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, and octadecyl (meth)acrylate. The alkyl (meth)acrylate may be n-butyl (meth)acrylate.
[0058] The amount of the (meth)acrylic acid alkyl ester in 100 parts by weight of the monomer group is, for example, 40 parts by weight or more, and may be 50 parts by weight or more, 60 parts by weight or more, 70 parts by weight or more, 80 parts by weight or more, 85 parts by weight or more, 90 parts by weight or more, and further may be 95 parts by weight or more. It should be noted that when calculating the amount of a specific monomer, the weight of the partial polymer is converted into the weight of each monomer before polymerization.
[0059] The monomer group may include a carboxyl-containing monomer. The carboxyl-containing monomer may be a (meth) acrylic monomer, in other words, the (meth) acrylic monomer may include a carboxyl-containing monomer. Examples of carboxyl-containing monomers are (meth) acrylic acid, (meth) carboxylethyl acrylate, (meth) carboxylpentyl acrylate, itaconic acid, maleic acid, fumaric acid and crotonic acid. The amount of the carboxyl-containing monomer in 100 parts by weight of the monomer group is, for example, less than 10 parts by weight, and may be less than 9 parts by weight, less than 8 parts by weight, less than 7 parts by weight, less than 6 parts by weight, less than 5 parts by weight, less than 4.8 parts by weight, less than 4 parts by weight, less than 3 parts by weight, less than 2 parts by weight, less than 1 part by weight, and further may be less than 0.5 parts by weight. The lower limit of the amount of the compounding is, for example, more than 0.1 parts by weight, and may be more than 0.5 parts by weight as the case may be. The monomer group may also not include a carboxyl-containing monomer.
[0060] The monomer group may include a hydroxyl-containing monomer. The hydroxyl-containing monomer may be a (meth) acrylic monomer, in other words, the (meth) acrylic monomer may include a hydroxyl-containing monomer. The hydroxyl-containing monomer may contribute to the improvement of the cohesive force of the adhesive sheet. Examples of hydroxyl-containing monomers are 2-hydroxyethyl (meth) acrylate, 2-hydroxypropyl (meth) acrylate, 4-hydroxybutyl (meth) acrylate, 6-hydroxyhexyl (meth) acrylate, 8-hydroxyoctyl (meth) acrylate, 10-hydroxydecyl (meth) acrylate, 12-hydroxylauryl (meth) acrylate, and (4-hydroxymethylcyclohexyl) methyl acrylate. The hydroxyl-containing monomer is preferably 2-hydroxyethyl (meth) acrylate and 4-hydroxybutyl (meth) acrylate.
[0061] As described above, the amount of the hydroxyl-containing monomer in 100 parts by weight of the monomer group is less than 5 parts by weight. The amount of the hydroxyl-containing monomer is preferably less than 4 parts by weight, less than 3 parts by weight, less than 2 parts by weight, and further less than 1 part by weight. The lower limit of the amount is, for example, more than 0.01 parts by weight, more than 0.03 parts by weight, and further more than 0.05 parts by weight. The monomer group may not contain a hydroxyl-containing monomer.
[0062] The monomer group may include an ether group-containing monomer. The ether group-containing monomer may be a (meth)acrylic monomer, in other words, the (meth)acrylic monomer may include an ether group-containing monomer. The ether group-containing monomer may contribute to improving the anchoring force between the adhesive sheet 1 and the optical film.
[0063] The ether group-containing monomer is preferably an alkoxy group-containing monomer. Examples of the alkoxy group-containing monomer include alkylene oxide adducts represented by the following chemical formula (1). 1 is a hydrogen atom or a methyl group. 2 is an alkyl group. The alkyl group may be linear or branched. 2 Preferably, it is a straight-chain alkyl group. 2 Examples of the group are methyl and ethyl. n in formula (1) is an integer of 1 to 30, preferably an integer of 1 to 12, and may be an integer of 1 to 5.
[0064] [Chemical formula 1]
[0065]
[0066] Examples of the alkylene oxide adduct represented by formula (1) are 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 2-(2-ethoxyethoxy)ethyl (meth)acrylate, methoxytriethylene glycol (meth)acrylate, and methoxypolyethylene glycol (meth)acrylate, preferably 2-methoxyethyl acrylate (MEA).
[0067] The ether group-containing monomer is not limited to the above-mentioned alkylene oxide adduct. The ether group-containing monomer may have a ring structure, and the ring structure may have an ether group. Examples of the ring structure having an ether group include tetrahydrofuran ring, dihydrofuran ring, Alkane ring, etc. Examples of the ether group-containing monomer having a ring structure are cyclic trimethylolpropane formal (meth)acrylate and tetrahydrofurfuryl (meth)acrylate.
[0068] The amount of the ether group-containing monomer in 100 parts by weight of the monomer group is, for example, 1 part by weight or more, 5 parts by weight or more, 10 parts by weight or more, 20 parts by weight or more, 25 parts by weight or more, 30 parts by weight or more, 40 parts by weight or more, 50 parts by weight or more, 60 parts by weight or more, 70 parts by weight or more, 80 parts by weight or more, and further 90 parts by weight or more. The upper limit of the amount is, for example, 99 parts by weight or less, and may be 50 parts by weight or less depending on the circumstances. The monomer group may not contain the ether group-containing monomer.
[0069] In the photocurable composition, each of the above monomers may be included in the form of a partial polymer. The partial polymer may be any polymer of a homopolymer and a copolymer. The partial polymer may contribute to the stable formation of the coating layer described later by appropriately increasing the viscosity of the photocurable composition.
[0070] The photocurable composition generally contains a photopolymerization initiator. Examples of the photopolymerization initiator include a photoradical generator that generates radicals by visible light and / or ultraviolet light having a wavelength shorter than 450 nm.
[0071] Examples of photopolymerization initiators include benzoin ethers such as benzoin methyl ether, benzoin isopropyl ether, and benzoin dimethyl ether; substituted benzoin ethers such as anisole methyl ether; substituted acetophenones such as 2,2-diethoxyacetophenone and 2,2-dimethoxy-2-phenylacetophenone; α-hydroxyalkyl phenones such as 1-hydroxycyclohexyl phenyl ketone; substituted α-ol ketones such as 2-methyl-2-hydroxypropiophenone; aromatic sulfonyl chlorides such as 2-naphthalenesulfonyl chloride; photoactive oximes such as 1-phenyl-1,1-propanedione-2-(o-ethoxycarbonyl)-oxime; benzophenone, benzoylbenzoic acid, benzoylbenzoic acid, Benzophenone compounds such as methyl benzoate, 4-phenylbenzophenone, hydroxybenzophenone, acryloyl benzophenone, 4-benzoyl-4'-methyldiphenyl sulfide, 3,3',4,4'-tetra(tert-butylperoxycarbonyl)benzophenone; thioxanthone compounds such as thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, isopropylthioxanthone, 2,4-diisopropylthioxanthone, 2,4-diethylthioxanthone; 2,4,6-trichloro-s-triazine, 2-phenyl-4,6-bis(trichloromethyl)-s-triazine, 2-(p-methoxyphenyl)-4,6 -bis(trichloromethyl)-s-triazine, 2-(p-tolyl)-4,6-bis(trichloromethyl)-s-triazine, 2-piperonyl-4,6-bis(trichloromethyl)-s-triazine, 2,4-bis(trichloromethyl)-6-phenylvinyl-s-triazine, 2-(naphthalene-1-yl)-4,6-bis(trichloromethyl)-s-triazine, 2-(4-methoxy-naphthalene-1-yl)-4,6-bis(trichloromethyl)-s-triazine, 2,4-trichloromethyl-(piperonyl)-6-triazine, 2,4-trichloromethyl-(4'-methoxyphenylvinyl)-6-triazine, etc. Oxime ester compounds such as 1,2-octanedione, 1-[4-(phenylthio)-, 2-(O-benzoyloxime)], O-(acetyl)-N-(1-phenyl-2-oxo-2-(4'-methoxy-naphthyl)ethylidene)hydroxylamine; phosphine compounds such as bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide and 2,4,6-trimethylbenzoyldiphenylphosphine oxide; quinone compounds such as 9,10-phenanthrenequinone, camphorquinone, and ethylanthraquinone; borate ester compounds; carbazole compounds; imidazole compounds; and titanocene compounds. The photocurable composition may contain one or more photopolymerization initiators.
[0072] The amount of the photopolymerization initiator in the photocurable composition may be, for example, 0.02 to 10 parts by weight, or 0.05 to 5 parts by weight, relative to 100 parts by weight of the total of the monomer group and the partially polymerized product thereof.
[0073] As described above, the photocurable composition contains an isocyanate crosslinking agent. As the isocyanate crosslinking agent, a compound having at least two isocyanate groups (isocyanate compound) can be used. The number of isocyanate groups contained in the isocyanate compound is preferably 3 or more. The upper limit of the number of isocyanate groups is not particularly limited, for example, 5. As the isocyanate compound, aromatic isocyanate compounds, alicyclic isocyanate compounds, aliphatic isocyanate compounds, etc. can be cited.
[0074] Examples of the aromatic isocyanate compound include phenylene diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 2,2′-diphenylmethane diisocyanate, 4,4′-diphenylmethane diisocyanate, 4,4′-toluidine diisocyanate, 4,4′-diphenyl ether diisocyanate, 4,4′-diphenyl diisocyanate, 1,5-naphthalene diisocyanate, and xylylene diisocyanate.
[0075] Examples of the alicyclic isocyanate compound include 1,3-cyclopentene diisocyanate, 1,3-cyclohexane diisocyanate, 1,4-cyclohexane diisocyanate, isophorone diisocyanate, hydrogenated diphenylmethane diisocyanate, hydrogenated xylylene diisocyanate, hydrogenated toluene diisocyanate, and hydrogenated tetramethylxylylene diisocyanate.
[0076] Examples of the aliphatic isocyanate compound include trimethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate (HDI), pentamethylene diisocyanate (PDI), 1,2-propylene diisocyanate, 1,3-butylene diisocyanate, dodecamethylene diisocyanate, and 2,4,4-trimethylhexamethylene diisocyanate.
[0077] As isocyanate crosslinking agents, there can also be mentioned polymers (dimers, trimers, pentamers, etc.) of the above-mentioned isocyanate compounds, adducts obtained by addition of polyols such as trimethylolpropane, urea-modified products, biuret-modified products, allophanate-modified products, isocyanurate-modified products, carbodiimide-modified products, and urethane prepolymers obtained by addition of polyether polyols, polyester polyols, acrylic polyols, polybutadiene polyols, polyisoprene polyols, etc.
[0078] The isocyanate crosslinking agent preferably comprises an aliphatic isocyanate compound and / or a derivative of an aliphatic isocyanate compound. The isocyanate crosslinking agent is particularly preferably at least one selected from pentamethylene diisocyanate (PDI) crosslinking agents (PDI and its derivatives) and hexamethylene diisocyanate (HDI) crosslinking agents (HDI and its derivatives). Specific examples of PDI crosslinking agents include isocyanurate modified products of PDI, etc. Specific examples of HDI crosslinking agents include isocyanurate modified products of HDI, biuret modified products, etc.
[0079] As described above, the amount of the isocyanate crosslinking agent is 0.02 parts by weight or more, preferably 0.05 parts by weight or more, and can be 0.1 parts by weight or more, 0.5 parts by weight or more, 1 parts by weight or more, 1.5 parts by weight or more, and further can be 2 parts by weight or more, relative to a total of 100 parts by weight of the monomer group and its partial polymer. The upper limit of the amount is, for example, 5 parts by weight or less, and can be 3 parts by weight or less.
[0080] The ratio NCO / OH of the amount of isocyanate groups present in the photocurable composition (particularly the amount of isocyanate groups contained in the isocyanate crosslinking agent) to the amount of hydroxyl groups present in the photocurable composition (particularly the amount of hydroxyl groups contained in the hydroxyl-containing monomer) is, for example, 0.02 or more, 0.05 or more, 0.1 or more, 0.5 or more, 1.0 or more, and further 1.5 or more. The upper limit of the ratio NCO / OH is, for example, 5.0 or less, and may be 1.0 or less depending on the circumstances.
[0081] The photocurable composition may further contain other crosslinking agents other than isocyanate crosslinking agents. As other crosslinking agents, for example, a multifunctional monomer having two or more polymerizable functional groups in one molecule may be cited. The multifunctional monomer may be a (meth)acrylic monomer. Examples of multifunctional monomers are monomers having two or more C=C bonds in one molecule, and monomers having one or more C=C bonds and one or more epoxy groups, aziridine groups, Monomers having polymerizable functional groups such as oxazoline group, hydrazine group, methylol group, etc. Polyfunctional monomers are preferably monomers having two or more C═C bonds in one molecule.
[0082] Examples of the multifunctional monomer include: multifunctional acrylates (ester compounds formed by polyols and (meth)acrylic acid, etc.) such as (poly)ethylene glycol di(meth)acrylate, (poly)propylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, 1,2-ethylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol diacrylate (NDDA), 1,12-dodecanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, and tetramethylolmethane tri(meth)acrylate; allyl (meth)acrylate, vinyl (meth)acrylate, divinylbenzene, epoxy acrylate, polyester acrylate, urethane acrylate, butyl di(meth)acrylate, and hexyl di(meth)acrylate. The polyfunctional monomer is preferably a polyfunctional acrylate, and more preferably trimethylolpropane tri(meth)acrylate, hexanediol di(meth)acrylate, or dipentaerythritol hexa(meth)acrylate.
[0083] The amount of other crosslinking agents in the photocurable composition varies depending on the molecular weight, the number of functional groups, etc., and is, for example, 5 parts by weight or less, 3 parts by weight or less, 2 parts by weight or less, 1 part by weight or less, 0.5 parts by weight or less, 0.3 parts by weight or less, and further 0.1 parts by weight or less, relative to 100 parts by weight of the total of the monomer group and its partial polymer. The lower limit of the amount is, for example, 0.01 parts by weight or more, and further 0.05 parts by weight or more.
[0084] The photocurable composition may also contain additives other than those mentioned above. Examples of additives are chain transfer agents, reworkability improving agents, anticorrosive agents, silane coupling agents, viscosity modifiers, tackifiers, plasticizers, softeners, anti-aging agents, fillers, colorants, antioxidants, surfactants, antistatic agents, and ultraviolet light absorbers.
[0085] The content of the solvent in the photocurable composition is, for example, 5% by weight or less, 4% by weight or less, 3% by weight or less, 2% by weight or less, 1% by weight or less, and further 0.5% by weight or less. The photocurable composition may contain substantially no solvent. Substantially containing no solvent means that a solvent from an additive or the like is allowed to be contained at a content of, for example, 0.1% by weight or less, preferably 0.05% by weight or less, and more preferably 0.01% by weight or less.
[0086] The viscosity of the photocurable composition is preferably 5 to 150 poise. The photocurable composition having a viscosity within the above range is particularly suitable for forming a coating layer described below.
[0087] (Physical properties and characteristics of adhesive sheets)
[0088] In the adhesive sheet 1, the concentration of residual monomers, especially hydroxyl-containing monomers, is preferably 16000 ppm by weight or less. In this case, there is a tendency to suppress the reduction of the anchoring force between the adhesive sheet 1 and the optical film. The concentration of residual monomers is preferably 15000 ppm by weight or less, and can be 12000 ppm by weight or less, 10000 ppm by weight or less, 8000 ppm by weight or less, 7000 ppm by weight or less, 6000 ppm by weight or less, 5000 ppm by weight or less, 4000 ppm by weight or less, 3500 ppm by weight or less, 3000 ppm by weight or less, 2500 ppm by weight or less, 2000 ppm by weight or less, and further can be 1500 ppm by weight or less. The lower limit of the concentration of residual monomers is, for example, 300 ppm by weight or more. The concentration of residual monomers in the adhesive sheet 1 can be evaluated by gas chromatography (GC) analysis.
[0089] The polymerization rate of the monomer group in the pressure-sensitive adhesive sheet 1 is preferably 90% or more. The polymerization rate may be 95% or more, 98% or more, or even 99% or more.
[0090] The gel fraction of the pressure-sensitive adhesive sheet 1 may be, for example, 50% or more, 75% or more, 80% or more, or even 85% or more.
[0091] The creep amount of the adhesive sheet 1 is, for example, 500 μm or less, 300 μm or less, 180 μm or less, 160 μm or less, 150 μm or less, 100 μm or less, or 50 μm or less. The lower limit of the creep amount is, for example, 5 μm or more, 10 μm or more, or 20 μm or more.
[0092] The creep amount of the adhesive sheet 1 can be evaluated as follows (see Figure 2A and Figure 2B ). First, a laminate of the adhesive sheet 1 and the support film 51 to be evaluated is cut into a 10 mm × 50 mm strip to prepare a test piece 52. The support film 51 is arranged for the purpose of suppressing the deformation of the load-applying portion of the adhesive sheet 1 to which a load is applied during the test, thereby measuring the creep amount with higher accuracy. The support film 51 can use a resin film such as a polyethylene terephthalate (PET) film. The support film 51 can be an optical film or a laminate including an optical film. The thickness of the support film 51 can be a thickness that does not deform due to the above-mentioned load, for example, 20 to 200 μm. Next, as Figure 2A and Figure 2B As shown, the test piece 52 is attached to the surface of the stainless steel test plate 53 by using the adhesive sheet 1 with a bonding surface of 10 mm in length and 10 mm in width. Figure 2B yes Figure 2ASection BB. The test piece 52 is pasted to the test plate 53 in a manner that does not allow bubbles to be mixed between the test plate 53 and the adhesive sheet 1. In addition, after pasting, it is placed in an autoclave at 50°C and 5 atmospheres (absolute pressure) for 15 minutes to homogenize the bonding between the test plate 53 and the adhesive sheet 1. Next, the test plate 53 and the test piece 52 are vertically held in an atmosphere of 25°C in such a manner that the test plate 53 is on top and are placed for at least 5 minutes. With the test plate 53 fixed, a weight of 500g is fixed at the center of the lower end of the test piece 52, and a load 54 of 500gf is applied vertically downward. The creep amount (displacement amount) of the adhesive sheet 1 relative to the test plate 53 at the moment 3600 seconds after the start of the application of the load 54 is measured as the amount of weight dropped. The amount of weight dropped can be measured using a laser displacement meter.
[0093] The thickness of the adhesive sheet 1 is, for example, 500 μm or less, 250 μm or less, 150 μm or less, 100 μm or less, 50 μm or less, 30 μm or less, 25 μm or less, or 20 μm or less. The lower limit of the thickness of the adhesive sheet 1 is, for example, 2 μm or more, and 5 μm or more.
[0094] (Method for producing adhesive sheet)
[0095] The adhesive sheet 1 can be manufactured, for example, by the following method. Figure 3A , Figure 3B As shown in FIG. 1 , a first laminate 15 is prepared which includes a substrate sheet 21, a coating layer 22 containing a photocurable composition, and a release liner 23 in this order. By irradiating the first laminate 15 with light 14, a pressure-sensitive adhesive sheet 1 ( Figure 3C ).
[0096] Typically, the irradiation of the first stacked body 15 with the light 14 can be carried out from one side of the base sheet 21 ( Figure 3A At this time, the light 14 passes through the substrate sheet 21 and reaches the coating layer 22, thereby curing the coating layer 22. However, it should be noted that the irradiation of the light 14 can be implemented from one side of the release liner 23, or from both sides of the release liner 23 and the substrate sheet 21 ( Figure 3B The pressure-sensitive adhesive sheet 1 formed of the coating layer 22 is sandwiched between the base sheet 21 and the release liner 23 to constitute a part of the second laminate 16 until the release liner 23 is peeled off.
[0097] An example of the base material of the release liner 23 (hereinafter referred to as "base material") is a resin film. Examples of the resin that can be contained in the base material are polyesters such as polyethylene terephthalate and polyethylene naphthalate, acetate resins, polyether sulfone, polycarbonate, polyamide, polyimide, polyolefin, (meth) acrylic resin, polyvinyl chloride, polyvinylidene chloride, polystyrene, polyvinyl alcohol, polyarylate, and polyphenylene sulfide. The resin is preferably a polyester such as polyethylene terephthalate.
[0098] The release liner 23 may have the transmittance of the light 14 or may have the same degree of transmittance of the light 14 as the base sheet 21 .
[0099] The thickness of the release liner 23 is, for example, 10 to 200 μm, or 25 to 150 μm.
[0100] The release liner 23 may include a layer other than the lining substrate. The release liner 23 may include a release layer. The release liner 23 may include, for example, a lining substrate and a release layer formed on one side of the lining substrate. The release liner 23 may be used in a manner such that the release layer is on the coating layer 22 side.
[0101] Typically, the release layer is a cured layer of a release agent composition containing a release agent. The release agent can use various release agents such as silicone release agents, fluorine release agents, long-chain alkyl release agents, fatty acid amide release agents, and silica powder. The release liner 23 can have a cured layer of a release agent composition containing a silicone release agent as a main component (hereinafter, "silicone release layer"). The silicone release layer is particularly suitable for balancing the adhesion and releasability relative to the adhesive sheet 1. It should be noted that in this specification, the main component refers to the component with the largest content.
[0102] The silicone release agent includes various curable silicone materials such as addition reaction type, condensation reaction type, ultraviolet curing type, electron beam curing type, solvent-free type, etc., preferably addition reaction curing type silicone materials. Addition reaction curing type silicone materials are particularly suitable for forming a release layer that takes into account both adhesion and peelability with respect to the adhesive sheet 1. The curable silicone material can be a silicone modified resin obtained by introducing reactive silicone into an organic resin such as urethane, epoxy, alkyd resin, etc. by graft polymerization.
[0103] Examples of addition reaction curing silicone materials are polyorganosiloxanes having vinyl or alkenyl groups in the molecule. Addition reaction curing silicone materials may not have hydrosilyl groups. Examples of alkenyl groups are 3-butenyl, 4-pentenyl, 5-hexenyl, 6-heptenyl, 7-octenyl, 8-nonenyl, 9-decenyl, 10-undecenyl and 11-dodecenyl. Examples of polyorganosiloxanes are copolymers of polyalkylalkylsiloxanes such as polydimethylsiloxane, polydiethylsiloxane and polymethylethylsiloxane, polyalkylarylsiloxane, and poly(dimethylsiloxane-diethylsiloxane) and other monomers containing Si atoms. Polyorganosiloxane is preferably polydimethylsiloxane.
[0104] A mold release composition containing a silicone-based mold release agent as a main component (hereinafter, "silicone mold release composition") generally contains a crosslinking agent. An example of the crosslinking agent is a polyorganosiloxane having a hydrosilyl group. The crosslinking agent may have two or more hydrosilyl groups in one molecule.
[0105] The silicone release agent composition may also contain a curing catalyst. Examples of the curing catalyst are platinum catalysts. Examples of platinum catalysts are chloroplatinic acid, olefin complexes of platinum, and olefin complexes of chloroplatinic acid. The amount of the platinum catalyst used is, for example, 10 to 1000 ppm (weight basis, converted to platinum) relative to the total solid content of the composition.
[0106] The silicone release agent composition may also contain additives. Examples of additives are release control agents and adhesion improvers. Examples of release control agents are unreactive silicone resins, and more specifically, organosiloxanes such as octamethylcyclotetrasiloxane and MQ resins. The total amount of release control agents and adhesion improvers is, for example, 1 to 30% by weight relative to the total solid content of the composition. Other examples of additives are fillers, antistatic agents, antioxidants, ultraviolet absorbers, plasticizers, and colorants. The total amount of other additives is, for example, 10% by weight or less relative to the total solid content of the composition.
[0107] The silicone release agent composition may also contain an organic solvent. Examples of organic solvents are hydrocarbon solvents such as cyclohexane, n-hexane, and n-heptane; aromatic solvents such as toluene and xylene; ester solvents such as ethyl acetate and methyl acetate; ketone solvents such as acetone and methyl ethyl ketone; and alcohol solvents such as methanol, ethanol, and butanol. Two or more organic solvents may also be contained. The amount of organic solvent used is preferably 80 to 99.9% by weight of the silicone release agent composition.
[0108] The release layer can be formed, for example, by heating and drying a coating film containing a release agent composition formed on a lining substrate. The release agent composition can be applied by various coating methods such as roller coating, roller lick coating, gravure coating, reverse coating, roller brush, spray coating, dip roller coating, rod coating, blade coating, air knife coating, shower coating, die lip coating, and die coating. Heating and drying can be performed by hot air drying, for example. The heating temperature and time vary depending on the heat resistance of the lining substrate, and are generally 80 to 150° C. and about 10 seconds to 10 minutes. As required, irradiation with active energy rays such as ultraviolet rays can also be used in combination.
[0109] The thickness of the release layer is, for example, 10 to 300 nm. The upper limit of the thickness may be 200 nm or less, 150 nm or less, 120 nm or less, 110 nm or less, 100 nm or less, less than 100 nm, 90 nm or less, 80 nm or less, 70 nm or less, less than 70 nm, and further may be 65 nm or less. The lower limit of the thickness may be 15 nm or more, 20 nm or more, 25 nm or more, 30 nm or more, 35 nm or more, 40 nm or more, 45 nm or more, and further may be 50 nm or more.
[0110] The release liner 23 may be in the form of a single sheet or in the form of a long strip.
[0111] An example of the base sheet 21 is a resin film. Examples of the resin contained in the base sheet 21 are the same as examples of the resin that can be contained in the backing base.
[0112] It is preferred that the base sheet 21 has excellent transmittance to the light 14 .
[0113] The thickness of the base sheet 21 is, for example, 10 to 200 μm, or 25 to 150 μm.
[0114] The substrate sheet 21 may have a release layer on the surface of the coating layer 22 side. The examples of the release layer and its preparation method that the substrate sheet 21 may have are the same as the examples of the release layer and its preparation method that the release liner 23 may have. It is also possible to have a release layer on both the release liner 23 and the substrate sheet 21. In this case, the release layers of the two may be formed by a release agent composition containing the same release agent as a main component. In addition, the thickness of the release layers of the two may be different, for example, the release layer of the substrate sheet 21 may be thicker.
[0115] The base sheet 21 can generally be selected to have a greater release force with the pressure-sensitive adhesive sheet 1 than the release liner 23 .
[0116] The base sheet 21 may be in a single sheet shape or in a long strip shape.
[0117] The first laminate 15 can be formed, for example, by forming a coating layer 22 on a substrate sheet 21 (or a release liner 23), and disposing a release liner 23 (or a substrate sheet 21) on the formed coating layer 22. Alternatively, the first laminate 15 can be formed by coating the photocurable composition so as to flow into a space between the substrate sheet 21 and the release liner 23, which are maintained at a predetermined interval so that their main surfaces face each other.
[0118] The coating layer 22 can be formed by various coating methods such as roll coating, lick roll coating, gravure coating, reverse coating, roller brushing, spray coating, dip roll coating, rod coating, blade coating, air knife coating, shower coating, die lip coating, and die coating.
[0119] The thickness of the coating layer 22 can be adjusted according to the target thickness of the adhesive sheet 1, and may be, for example, 5 to 500 μm, 5 to 250 μm, 5 to 150 μm, 5 to 100 μm, 5 to 50 μm, 5 to 30 μm, 5 to 25 μm, or even 5 to 20 μm.
[0120] The light 14 irradiated to the first stack 15 is, for example, visible light or ultraviolet light having a wavelength shorter than 450 nm. The light 14 may include light of a wavelength in the same region as the absorption wavelength of the photopolymerization initiator contained in the photocurable composition. The light 14 obtained by cutting off short-wavelength light with a wavelength of less than 300 nm through an optical filter or the like may be irradiated, and cutting off the short-wavelength light is suitable for suppressing the degradation of the substrate sheet 21 caused by the light 14. The light source of the light 14 is, for example, an irradiation device having an ultraviolet irradiation lamp. Examples of ultraviolet irradiation lamps are ultraviolet LEDs, low-pressure mercury lamps, medium-pressure mercury lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, metal halide lamps, xenon lamps, microwave-excited mercury lamps, black light lamps, chemical lamps, sterilization lamps, low-pressure discharge mercury lamps, and excimer lasers. Two or more ultraviolet irradiation lamps may also be combined.
[0121] The irradiation of the light 14 may be continuous or intermittent.
[0122] The illuminance of the light 14 is, for example, 1 to 20 mW / cm 2 The irradiation time of the light 14 is, for example, 5 minutes to 5 hours. The cumulative light intensity of the light 14 on the first stack 15 is, for example, 100 to 5000 mJ / cm 2 .
[0123] If necessary, the release liner 23 may be peeled off from the second laminate 16 to expose the surface (eg, surface 1 a ) of the pressure-sensitive adhesive sheet 1 , and the surface may be subjected to a surface modification treatment.
[0124] [Embodiments of optical laminate]
[0125] An example of the optical layered body of the present embodiment is shown in Figure 4 . Figure 4 The optical laminate 10 comprises the above-mentioned adhesive sheet 1 and at least one optical film 2 selected from a polarizing film and a phase difference film. The adhesive sheet 1 is preferably directly in contact with the optical film 2. Figure 4 In the example, the surface 1a of the pressure-sensitive adhesive sheet 1 is in contact with the optical film 2. The optical laminate 10 may have a structure in which a base sheet used when producing the pressure-sensitive adhesive sheet 1 is laminated on the pressure-sensitive adhesive sheet 1. The optical laminate 10 can be used as an optical film with a pressure-sensitive adhesive sheet.
[0126] (Optical Film)
[0127] The optical film 2 has a surface 2a opposite to the adhesive sheet 1. For example, the surface 2a is in contact with the surface 1a of the adhesive sheet 1. The surface 2a of the optical film 2 is subjected to a surface modification treatment. According to the surface 2a subjected to the surface modification treatment, there is a tendency to improve the anchoring force between the adhesive sheet 1 and the optical film 2. As the surface modification treatment, the surface modification treatment described above for the adhesive sheet 1 can be cited.
[0128] The surface 2a is preferably subjected to a corona treatment as a surface modification treatment. When the surface 2a is subjected to a corona treatment, the conditions such as the discharge amount can be appropriately adjusted within the range described above for the pressure-sensitive adhesive sheet 1, for example.
[0129] As described above, the optical film 2 includes at least one selected from a polarizing film and a phase difference film. The optical film 2 may be a laminated film including a polarizing film and / or a phase difference film. The optical film 2 may include a film made of glass. However, the optical film 2 is not limited to the above examples.
[0130] The polarizing film includes a polarizer. Typically, the polarizing film includes a polarizer and a protective film (transparent protective film). The protective film is, for example, arranged in contact with the main surface (surface with the widest area) of the polarizer. The polarizer can be arranged between two protective films. The protective film can be arranged on at least one side of the polarizer.
[0131] The polarizer is not particularly limited, and examples thereof include: a polarizer obtained by adsorbing a dichroic substance such as iodine and a dichroic dye on a hydrophilic polymer film such as a polyvinyl alcohol film, a partially formalized polyvinyl alcohol film, and a partially saponified film of an ethylene-vinyl acetate copolymer, and then uniaxially stretching the film; a polyene oriented film such as a dehydrated product of polyvinyl alcohol and a dehydrochlorinated product of polyvinyl chloride, etc. Typically, the polarizer is formed of a polyvinyl alcohol film (polyvinyl alcohol films include partially saponified films of ethylene-vinyl acetate copolymers) and a dichroic substance such as iodine.
[0132] The thickness of the polarizer is not particularly limited, for example, it is 80 μm or less, it can be 50 μm or less, 30 μm or less, 25 μm or less, and further, it can be 20 μm or less. The lower limit of the thickness of the polarizer is not particularly limited, for example, it is 1 μm or more, it can be 5 μm or more, 10 μm or more, and further, it can be 15 μm or more. The dimensional change of the thin polarizer (for example, the thickness is 20 μm or less) is suppressed, which can contribute to the durability of the optical laminate, especially the durability at high temperature.
[0133] As the material of the protective film, for example, a thermoplastic resin having excellent transparency, mechanical strength, thermal stability, moisture barrier, isotropy, etc. can be used. Specific examples of such thermoplastic resins include cellulose resins such as cellulose triacetate, polyester resins, polyethersulfone resins, polysulfone resins, polycarbonate resins, polyamide resins, polyimide resins, polyolefin resins, (meth)acrylic resins, cyclic polyolefin resins (norbornene resins), polyarylate resins, polystyrene resins, polyvinyl alcohol resins, and mixtures thereof. The material of the protective film can be a thermosetting resin or ultraviolet curing resin such as (meth)acrylic acid, urethane, acrylic urethane, epoxy, silicone, etc. In the case where the polarizing film has two protective films, the materials of the two protective films can be the same or different from each other. For example, a protective film formed of a thermoplastic resin can be bonded to one main surface of the polarizer via an adhesive, and a protective film formed of a thermosetting resin or an ultraviolet curing resin can be bonded to the other main surface of the polarizer. The protective film can contain one or more arbitrary additives. Examples of the additive include ultraviolet absorbers, antioxidants, lubricants, plasticizers, release agents, anti-coloring agents, flame retardants, nucleating agents, antistatic agents, pigments, and colorants.
[0134] It should be noted that the film containing (meth) acrylic resin has a tendency to have a low bonding strength with the adhesive sheet. However, according to the adhesive sheet 1 of this embodiment, even when in contact with the surface of the protective film containing (meth) acrylic resin, the anchoring force with the optical film 2 can be adjusted to a sufficiently high value.
[0135] The thickness of the protective film can be appropriately determined, and is generally about 10 to 200 μm from the perspectives of strength, workability such as handling properties, and thin film properties.
[0136] The polarizer and the protective film are usually bonded together via a water-based adhesive or the like. Examples of the water-based adhesive include isocyanate adhesives, polyvinyl alcohol adhesives, gelatin adhesives, vinyl latex, water-based polyurethane, and water-based polyester. Other adhesives other than the above-mentioned adhesives include ultraviolet curing adhesives and electron beam curing adhesives. Electron beam curing polarizer adhesives show suitable adhesion to various protective films. The adhesive may also contain a metal compound filler.
[0137] In the polarizing film, a retardation film or the like may be formed on the polarizer instead of the protective film. Another protective film or a retardation film or the like may be provided on the protective film.
[0138] The protective film may be provided with a hard coating layer on the surface opposite to the surface bonded to the polarizer, and may be subjected to treatment for the purpose of anti-reflection, anti-blocking, diffusion, anti-glare, etc.
[0139] The polarizing film may be a circular polarizing film.
[0140] As the retardation film, a film obtained by stretching a polymer film or a film obtained by orienting and fixing a liquid crystal material can be used. The retardation film has birefringence in the plane and / or in the thickness direction, for example.
[0141] The phase difference film includes a phase difference film for antireflection (refer to Japanese Patent Application Publication No. 2012-133303
[0221] ,
[0222] , and
[0228] ), a phase difference film for viewing angle compensation (refer to Japanese Patent Application Publication No. 2012-133303
[0225] and
[0226] ), and a tilted orientation phase difference film for viewing angle compensation (refer to Japanese Patent Application Publication No. 2012-133303
[0227] ).
[0142] The specific structure of the retardation film, such as the retardation value, the arrangement angle, the three-dimensional birefringence, whether it is a single layer or a multilayer, etc., is not particularly limited, and a known retardation film can be used.
[0143] The thickness of the retardation film is preferably 20 μm or less, more preferably 10 μm or less, further preferably 1 to 9 μm, particularly preferably 3 to 8 μm.
[0144] The phase difference film may include, for example, a quarter wave plate and / or a half wave plate in which a liquid crystal material is oriented and fixed.
[0145] (Characteristics of Optical Laminated Body)
[0146] In the present embodiment, there is a tendency that the anchoring force F between the adhesive sheet 1 and the optical film 2 is large. The anchoring force F is, for example, 10.0 N / 25 mm or more, and may be 11.0 N / 25 mm or more, 12.0 N / 25 mm or more, 13.0 N / 25 mm or more, 14.0 N / 25 mm or more, 15.0 N / 25 mm or more, 16.0 N / 25 mm or more, 17.0 N / 25 mm or more, 18.0 N / 25 mm or more, 19.0 N / 25 mm or more, and may further be 20.0 N / 25 mm or more. Preferably, the anchoring force F is greater than 16.0 N / 25 mm. When the anchoring force F is large to this extent, the peeling between the adhesive sheet 1 and the optical film 2 can be fully suppressed. The upper limit of the anchoring force F is not particularly limited, and may be, for example, 50 N / 25 mm or less, and may be 30 N / 25 mm or less.
[0147] The anchoring force F of the adhesive sheet 1 and the optical film 2 can be measured by the following method. First, the optical laminate 10 to be evaluated is cut into a width of 25 mm × a length of 150 mm to make a test piece. Next, the entire surface of the optical film 2 possessed by the test piece is superimposed on the stainless steel test plate via a double-sided tape, and a 2 kg roller is reciprocated once to press them together. Next, the adhesive sheet 1 possessed by the test piece is superimposed on the evaluation sheet, and a 2 kg roller is reciprocated once to press them together. The evaluation sheet has a size of 30 mm in width × 150 mm in length, and is not particularly limited as long as it does not peel off from the adhesive sheet 1 during the test. As an evaluation sheet, for example, an ITO film (125Tetoraito OES (manufactured by Oike Industries, Ltd.) etc.) can be used. Next, using a commercially available tensile testing machine, the pressure-sensitive adhesive sheet 1 was peeled off from the optical film 2 at a peeling angle of 180° and a tensile speed of 300 mm / min while holding the evaluation sheet, and the average value of the peeling force at this time was determined as the anchoring force F between the pressure-sensitive adhesive sheet 1 and the optical film 2. It should be noted that the above test was performed in an atmosphere of 23°C.
[0148] Another example of the optical layered body of the present embodiment is shown in Figure 5 . Figure 5 The optical laminate 11 has a laminated structure in which the adhesive sheet 1A, the optical film 2A, the adhesive sheet 1B, and the optical film 2B are laminated in this order. The optical laminate 11 may have a structure in which the base sheet used when producing the adhesive sheet 1A is laminated on the adhesive sheet 1A.
[0149] In the optical laminate 11, typically, the optical film 2A is a phase difference film, and the optical film 2B is a polarizing film. The adhesive sheet 1B functions as an interlayer adhesive between the optical films 2A and 2B. The adhesive sheet 1B may be one using a known adhesive.
[0150] The optical layered body of the present embodiment can be distributed and stored in the form of a roll body in which a belt-shaped optical layered body is rolled up, or in the form of a single sheet-shaped optical layered body.
[0151] Typically, the optical laminate of this embodiment can be used in an image display device. The image display device can be formed by, for example, bonding the optical laminate 10 or 11 to an image display panel. The bonding is performed, for example, by an adhesive sheet 1. The image display device can be an organic EL display or a liquid crystal display. However, the image display device is not limited to the above examples. The image display device can also be a field luminescence (EL) display, a plasma display (PD), a field emission display (FED: Field Emission Display), etc. The image display device can be used for household appliances, in-vehicle uses, public information displays (PID) uses, etc.
[0152] Example
[0153] Hereinafter, the present invention will be described in more detail by way of examples. However, the present invention is not limited to the examples shown below.
[0154] [Polarizing film D1]
[0155] A long roll of a polyvinyl alcohol (PVA) resin film with a thickness of 30 μm (manufactured by Kuraray Co., Ltd., product name "PE3000") was subjected to uniaxial stretching while being subjected to swelling, dyeing, crosslinking, washing treatment, and further subjected to drying treatment, thereby obtaining a polarizer with a thickness of 12 μm. The uniaxial stretching was performed using a roll stretching machine so that the stretching ratio in the longitudinal direction reached 5.9 times. Specifically, in the swelling treatment, the film was stretched to 2.2 times while being treated in pure water at 20°C. In the dyeing treatment, the film was stretched to 1.4 times while being treated at 30°C in an aqueous solution in which the iodine concentration was adjusted so that the monomer transmittance of the obtained polarizer reached 45.0%. In the above aqueous solution, the weight ratio of iodine to potassium iodide was 1:7. As a crosslinking treatment, a two-stage crosslinking treatment was adopted. In the first stage of the crosslinking treatment, the film was stretched to 1.2 times while being treated in a boric acid / potassium iodide aqueous solution at 40°C. The boric acid content of the aqueous solution was 5.0%, and the potassium iodide content was 3.0%. In the second stage of crosslinking treatment, the film was stretched to 1.6 times while being treated in a boric acid / potassium iodide aqueous solution at 65°C. The boric acid content of the aqueous solution was 4.3%, and the potassium iodide content was 5.0%. In the washing treatment, a potassium iodide aqueous solution at 20°C was used. The potassium iodide content of the aqueous solution for washing treatment was 2.6%. The drying treatment was carried out at 70°C for 5 minutes.
[0156] Next, a TAC-HC film having a hard coating (HC) layer with a thickness of 32 μm on one side of a triacetylcellulose (TAC) film was bonded to one side of the above-mentioned polarizer using a PVA-based adhesive. Furthermore, an unstretched cycloolefin polymer (COP) film with a thickness of 13 μm was bonded to the other side of the polarizer using a PVA-based adhesive. Thus, a polarizing film D1 having a structure of a TAC protective layer / PVA polarizer / COP protective layer was prepared. Furthermore, the discharge amount was 63 W / m 2 ·min The surface of the polarizing film D1 on the COP film side was subjected to a corona treatment.
[0157] [Polarizing film D2]
[0158] (40μm TAC film with HC)
[0159] In a resin solution (DIC Corporation, trade name: UNIDIC 17-806, solid content concentration: 80%) obtained by dissolving an ultraviolet curable resin monomer or oligomer containing urethane acrylate as the main component in butyl acetate, 5 parts by weight of a photopolymerization initiator (BASF Corporation, trade name: IRGACURE907) and 0.1 parts by weight of a leveling agent (DIC Corporation, trade name: GRANDIC PC4100) were added per 100 parts by weight of the solid content in the solution. Furthermore, cyclopentanone and propylene glycol monomethyl ether were added to the solution at a ratio of 45:55 so that the solid content concentration in the obtained solution was 36%, thereby preparing a hard coat forming material. The prepared hard coat forming material was applied to a triacetyl cellulose (TAC) film (Fuji Film Corporation, TJ40UL, thickness: 40 μm) so that the thickness of the hard coat after curing was 7 μm, thereby forming a coating film. The coating film was dried at 90°C for 1 minute and then irradiated with a high-pressure mercury lamp at a cumulative light intensity of 300 mJ / cm 2 The coating was cured by ultraviolet light to form a hard coating layer (HC). Thus, a 40 μm TAC film with HC was prepared.
[0160] (30μm acrylic film)
[0161] 8000 g of methyl methacrylate (MMA), 2,000 g of methyl 2-(hydroxymethyl)acrylate (MHMA), 10000 g of 4-methyl-2-pentanone (methyl isobutyl ketone, MIBK), and 5 g of n-dodecyl mercaptan were placed in a 30 L kettle reactor equipped with a stirring device, a temperature sensor, a condenser, and a nitrogen inlet pipe, and the temperature was raised to 105° C. while nitrogen was passed therethrough. When reflux occurred, 5.0 g of tert-butyl peroxyisopropyl carbonate (Kayacarbon BIC-7, manufactured by Kayaku AKZO Co., Ltd.) was added as a polymerization initiator, and a solution consisting of 10.0 g of tert-butyl peroxyisopropyl carbonate and 230 g of MIBK was added dropwise over 4 hours, and solution polymerization was carried out at about 105° C. to 120° C. under reflux, and aging was further carried out over 4 hours.
[0162] Next, 30 g of a mixture of stearyl phosphate / distearyl phosphate (Phoslex A-18, manufactured by Sakai Chemical Industry Co., Ltd.) was added to the obtained polymer solution, and a cyclocondensation reaction was carried out at about 90°C to 120°C for 5 hours under reflux. Next, the obtained polymer solution was introduced into a vented screw twin-screw extruder (φ=29.75 mm, L / D=30) with a barrel temperature of 260°C, a rotation speed of 100 rpm, a reduced pressure of 13.3 to 400 hPa (10 to 300 mmHg), 1 rear vent and 4 front vents at a processing rate of 2.0 kg / h in terms of the resin amount. In the extruder, a cyclocondensation reaction and devolatilization were further carried out, and extrusion was carried out, thereby obtaining transparent pellets of a polymer containing a lactone ring.
[0163] Next, the obtained pellets were mixed and extruded with acrylonitrile-styrene (AS) resin (TOYO ASAS20, manufactured by Toyo Styrene Co., Ltd.) at a mass ratio of 90 / 10 using a single screw extruder (screw 30 mmφ), thereby obtaining transparent pellets. The pellets were melt-extruded from a 400 mm wide hanger-type T die using a 50 mmφ single screw extruder to produce a film with a thickness of 120 μm. The produced film was stretched to 2.0 times in the longitudinal direction and 2.0 times in the transverse direction at a temperature of 150°C using a twin-screw stretching device, thereby obtaining a stretched film with a thickness of 30 μm (30 μm acrylic film).
[0164] (Polarizing filter)
[0165] Between rollers with different speed ratios, a polyvinyl alcohol film with a thickness of 45 μm was stretched to 3 times while being dyed in an iodine solution with a temperature of 30°C and a concentration of 0.3% for 1 minute. Next, it was immersed in an aqueous solution with a temperature of 60°C containing boric acid with a concentration of 4% and potassium iodide with a concentration of 10% for 0.5 minutes, and stretched to a total stretch ratio of 6 times. Next, it was immersed in an aqueous solution with a temperature of 30°C containing potassium iodide with a concentration of 1.5% for 10 seconds for washing, and then dried at 50°C for 4 minutes, thereby obtaining a polarizer with a thickness of 18 μm.
[0166] The surface of the TAC film side of the 40 μm TAC film with HC was bonded to one side of the obtained polarizer using a PVA adhesive. Furthermore, the 30 μm acrylic film was bonded to the other side of the polarizer using a PVA adhesive. Thus, a polarizing film D2 having a structure of TAC film / PVA polarizer / acrylic film was prepared. Furthermore, the discharge amount was 63 W / m 2 The surface of the polarizing film D2 on the acrylic film side was subjected to corona treatment.
[0167] [Release liner A]
[0168] 30 parts by weight of addition reaction curing silicone (LTC761 containing hexenyl polysiloxane, 30% toluene solution, manufactured by Dow Corning Toray), 0.9 parts by weight of release control agent (BY24-850 containing unreacted silicone resin, manufactured by Dow Corning Toray), 2 parts by weight of curing catalyst (SRX212 containing platinum catalyst, manufactured by Dow Corning Toray), and 1:1 volume ratio of toluene / hexane mixed solvent as diluent were mixed to obtain a silicone release agent composition. The concentration of silicone solid content in the release agent composition was 1.0% by weight. Next, the release agent composition was applied to one side of a liner substrate (Lumirror XD500P as a polyester film, 75 μm thick) using a wire bar, and heated at 130°C for 1 minute to prepare a release liner A having a release layer (60 nm thick) on one side.
[0169] [Release liner B]
[0170] A release liner B having a release layer (thickness 120 nm) on one surface was prepared by the same method as the release liner A except that the thickness of the release agent composition applied to the liner substrate was changed.
[0171] [Monomer slurry A1]
[0172] 99 parts by weight of n-butyl acrylate (BA) and 1 part by weight of 4-hydroxybutyl acrylate (HBA), 0.05 parts by weight of 1-hydroxycyclohexyl-phenyl ketone (Omnirad 184, manufactured by IGM Resins BV) and 0.05 parts by weight of 2,2-dimethoxy-1,2-diphenylethane-1-one (Omnirad 651, manufactured by IGM Resins BV) as photopolymerization initiators were placed in a four-necked flask and irradiated with ultraviolet rays in a nitrogen atmosphere to obtain a partially photopolymerized monomer syrup A1. The ultraviolet rays were irradiated until the viscosity of the liquid in the flask (measurement conditions: BH viscometer No. 5 rotor, 10 rpm, measurement temperature 30°C) reached about 20 Pa·s.
[0173] [Monomer slurries A2 and A3]
[0174] Monomer syrups A2 and A3 were prepared by the same method as that for monomer syrup A1 except that the monomers used were changed as shown in Table 1.
[0175] [Table 1]
[0176]
[0177] The abbreviations in Table 1 are as follows.
[0178] BA: n-butyl acrylate
[0179] HBA: 4-Hydroxybutyl Acrylate
[0180] Omnirad184: 1-Hydroxycyclohexyl-phenyl ketone (Omnirad184, manufactured by IGM Resins BV)
[0181] Omnirad651: 2,2-dimethoxy-1,2-diphenylethane-1-one (Omnirad651, manufactured by IGM Resins B.V.)
[0182] [Photocurable compositions C1 to C12]
[0183] Next, the monomer syrup and the crosslinking agent were mixed so as to have the compositions shown in the following Table 2, thereby obtaining photocurable compositions C1 to C12.
[0184] [Table 2]
[0185]
[0186] (*1) Ratio of the amount of isocyanate groups to the amount of hydroxyl groups in the photocurable composition
[0187] The abbreviations in Table 2 are as follows.
[0188] NDDA: 1,9-nonanediol diacrylate
[0189] D177N: Isocyanurate-modified hexamethylene diisocyanate (Mitsui Chemicals, Inc., TAKENATE D-177N)
[0190] D376N: Isocyanurate-modified pentamethylene diisocyanate (Mitsui Chemicals, Inc., STABIOD-376N)
[0191] D165N: Biuret-modified hexamethylene diisocyanate (Mitsui Chemicals, Inc., TAKENATE D-165N)
[0192] TKA100: Isocyanurate-modified hexamethylene diisocyanate (manufactured by Asahi Kasei Corporation, DURANATE TKA-100)
[0193] (Example 1)
[0194] The photocurable composition C1 was applied to the release layer of the release liner A using an applicator to form a coating layer (thickness 20 μm). Next, the release liner was arranged on the formed coating layer to obtain the first laminate. The release liner B was arranged so that the release layer and the coating layer were in contact. Next, the coating layer was exposed to light at an illumination of 2 mW / cm 2 The first laminate was irradiated with ultraviolet light (black light source) from the release liner A side for 15 minutes to photocure the coating layer, thereby forming a second laminate consisting of the release liner A, the adhesive sheet (thickness 20 μm) and the release liner B.
[0195] Next, the release liner B was peeled off from the second laminate, and the polarizing film D1 was placed on the exposed surface of the pressure-sensitive adhesive sheet to obtain an optical laminate of Example 1. The polarizing film D1 was placed so that the surface on the COP film side was in contact with the pressure-sensitive adhesive sheet.
[0196] (Examples 2 to 6 and Comparative Example 1)
[0197] Optical layered bodies of Examples 2 to 6 and Comparative Example 1 were obtained by the same method as in Example 1 except that the photocurable composition used was changed as shown in Table 3.
[0198] (Example 7)
[0199] An optical laminate of Example 7 was obtained by the same method as in Example 1 except that the polarizing film D2 was used instead of the polarizing film D1. In addition, the polarizing film D2 was arranged so that the surface on the acrylic film side was in contact with the pressure-sensitive adhesive sheet.
[0200] (Examples 8, 10 to 13, 15, 16 and Comparative Examples 2 to 5)
[0201] Except having changed the photocurable composition used as shown in Table 3, the same method as Example 7 was carried out to obtain optical laminated bodies of Examples 8, 10 to 13, 15, 16 and Comparative Examples 2 to 5.
[0202] (Example 9)
[0203] The release liner B was peeled off from the second laminate and the discharge amount was 61 W / m 2 ·min An optical laminate of Example 9 was obtained by the same method as in Example 8 except that the exposed surface of the pressure-sensitive adhesive sheet was corona-treated and then the polarizing film D2 was disposed on the exposed surface.
[0204] (Example 14)
[0205] The release liner B was peeled off from the second laminate and the discharge amount was 61 W / m 2 ·min An optical laminate of Example 14 was obtained by the same method as in Example 13 except that the exposed surface of the pressure-sensitive adhesive sheet was corona-treated and then the polarizing film D2 was disposed on the exposed surface.
[0206] [Anchoring force]
[0207] For the optical laminates of the embodiments and comparative examples, the anchoring force F of the adhesive sheet and the polarizing film was measured by the above-mentioned method. As a double-sided tape, a product name "No.531" manufactured by Nitto Denko Corporation was used. As a stainless steel test plate, a SUS304 plate (width 40 mm × length 120 mm) was used. As an evaluation sheet, an ITO film (125 Tetoraito OES, manufactured by Oike Industries) was used. As a tensile testing machine, an Autograph SHIMAZU AG-I10KN (manufactured by Shimadzu Corporation) was used.
[0208] [Table 3]
[0209]
[0210] According to Table 3, compared with the comparative example, in the optical laminate of the embodiment using the adhesive sheet formed by the photocurable composition whose compounding amount of the hydroxyl-containing monomer and the isocyanate crosslinking agent is adjusted to the above range, the anchoring force F between the adhesive sheet and the optical film (polarizing film) is a larger value. In the optical laminate of Examples 9 and 14 in which the surface of the adhesive sheet is subjected to corona treatment, the anchoring force F between the adhesive sheet and the optical film is a particularly large value.
[0211] Industrial Applicability
[0212] The pressure-sensitive adhesive sheet of the present invention can be used for, for example, an optical layered body or an image display device.
Claims
1. An adhesive sheet formed from a photocurable composition comprising a monomer group and / or a partial polymer of the monomer group, In 100 parts by weight of the monomer group, the amount of the hydroxyl-containing monomer is less than 5 parts by weight. The photocurable composition comprises an isocyanate crosslinking agent, The amount of the isocyanate crosslinking agent blended is 0.02 parts by weight or more relative to 100 parts by weight of the total of the monomer group and the partial polymer.
2. The adhesive sheet according to claim 1, wherein The blending amount of the isocyanate crosslinking agent is 0.1 parts by weight or more relative to 100 parts by weight of the total of the monomer group and the partial polymer.
3. The adhesive sheet according to claim 1, wherein The ratio of the amount of isocyanate groups present in the photocurable composition to the amount of hydroxyl groups present in the photocurable composition is 0.02 or more.
4. The adhesive sheet according to claim 1, wherein The isocyanate-based cross-linking agent includes an aliphatic isocyanate compound and / or a derivative of the aliphatic isocyanate compound.
5. The adhesive sheet according to claim 1, wherein The isocyanate crosslinking agent is at least one selected from pentamethylene diisocyanate crosslinking agents and hexamethylene diisocyanate crosslinking agents.
6. The adhesive sheet according to claim 1, wherein The content of the solvent in the photocurable composition is 5% by weight or less.
7. The adhesive sheet according to claim 1, wherein The monomer group includes a (meth)acrylic monomer.
8. The adhesive sheet according to claim 1, wherein The concentration of the residual monomers was 16000 ppm by weight or less. 9 . The pressure-sensitive adhesive sheet according to claim 1 , which has a surface subjected to a surface modification treatment.
10. An optical laminate comprising: The adhesive sheet according to any one of claims 1 to 9, and An optical film including at least one selected from a polarizing film and a retardation film.
11. The optical layered body according to claim 10, wherein: The anchoring force between the pressure-sensitive adhesive sheet and the optical film is 10.0 N / 25 mm or more.
Citation Information
Patent Citations
Optical display device having polarizing film
JP2012133303A